Analisis Pengaruh Bonus Demografi Terhadap Pertumbuhan Ekonomi Di Sumatera Utara - Clawdya Zebua, Nobel Indah (Universitas Labuhanbatu, 2023)
Indonesia is predicted to experience a demographic bonus. Demographic Bonus is a country condition where the number of young people with an abundance of about 2/3 of the total population. This study aims to determine the Labor Force Participation Rate and Dependency Ratio on Economic Growth in North Sumatra, which is also experiencing a demographic bonus. The labor force is the population of working age or looking for work, so when they get a job and income, it will affect economic growth. The Dependency Ratio is the dependency ratio connecting groups that are most likely to become economically dependent groups. This study uses secondary data or time series. While the analysis used is multiple linear regression. This model tests the Labor Force Participation Rate and Dependency Ratio on economic growth in North Sumatra. This model shows that the Labor Force Participation Rate has a positive effect on economic growth in North Sumatra. The Dependency Ratio has a positive effect on Economic Growth in North Sumatra. Furthermore, simultaneously / simultaneously the Labor Force Participation Rate and Dependency Ratio have a positive and significant effect on Economic Growth in North Sumatra.